IMPLEMENTASI MANAJEMEN KURIKULUM MERDEKA DALAM MANAJEMEN BERBASIS SEKOLAH (MBS) TERHADAP SUMBER DAYA DI SD NEGERI 007 UJUNGBATU - Susanti, Dewi; Marhadi, Hendri; Nur Mustafa, M. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study aims to analyze the implementation of the Independent Curriculum in School-Based Management (SBM) on resources at SDN 007 Ujungbatu. The approach in this study uses a qualitative approach with a case study method. Data collection techniques include interviews, direct observation, and document analysis, involving teachers, principals, and educational staff. The results of the study indicate that the implementation of independent management in school-based management on resources is; 1) increasing enjoyable learning, 2) the Independent Curriculum provides a positive contribution to learning through an innovative, enjoyable, and student-oriented approach, 3) Maximizing the use of existing facilities and infrastructure to be appropriate to support the learning process, 4) improving the quality of human resources through continuous development opportunities for all school residents. through Several factors that support successful implementation include cooperation between teachers, institutional support, and the use of digital platforms such as the Merdeka Mengajar Platform (PMM). However, a number of obstacles are still found, including a lack of understanding among senior teachers, unequal access to professional training, and limited facilities and infrastructure. To address this, the school initiated structured training, mentoring between teachers, and empowered community participation. This study concluded that the effectiveness of the Independent Curriculum implementation depends not only on its design but also on school leadership, resource availability, and ongoing professional support. These findings contribute to policymakers and education practitioners in formulating strategies to strengthen curriculum reform at the elementary education level.